Development of stimulus material for research in alcohol use disorders. Issue 1 (12th October 2016) - Fey, Werner; Moggi, Franz; Rohde, Kristina B.; Michel, Chantal; Seitz, Andrea; Stein, Maria
Abstract: The availability of appropriate stimulus material is a key concern for an experimental approach to research on alcohol use disorders (AUDs). A large number of such stimuli are necessary to evoke relevant alcohol‐related associations. We report the development of a large stimulus database consisting of 457 pictures of alcoholic beverages and 398 pictures of neutral objects. These stimuli were rated by 18 inpatients hospitalized due to severe AUD and 18 healthy controls along four dimensions: arousal, valence, alcohol‐relatedness, and craving. Physical parameters of the pictures were assessed. After outlier removal, 831 stimuli that were characterized as either alcohol‐related or neutral were retained in the final stimulus pool. Alcohol‐related pictures (versus neutral pictures) evoked higher arousal, more craving and were judged to have higher alcohol‐relatedness and a more negative valence. Group comparisons indicated that in patients, neutral pictures evoked more craving and had higher alcohol‐relatedness than they did in controls. Physical parameters such as visual complexity, luminance, and color were extracted from these pictures, and extreme values were normalized to minimize mean differences between alcoholic and neutral stimuli. The pictures met the qualitative requirements for (neurophysiological) research. A data file containing rating values and physical parameters will be provided upon request.